Translational Detection of Indole by Complementary Cell-free Protein Synthesis Assay - Lee, You Jin; Lee, Soojin; Kim, Dong-Myung (Frontiers in Bioengineering and Biotechnology, 2022)
The information encoded in a single copy of DNA is processed into a plethora of protein molecules via the cascade of transcription and translation. Thus, the molecular process of gene expression can be considered an efficient biological amplifier from the viewpoint of synthetic biology. Cell-free protein synthesis (CFPS) enables the implementation of this amplification module for in vitro analysis of important biomolecules and avoids many of the problems associated with whole cell-based approaches. Here, we developed a method to analyze indole by using a combination of enzymatic conversion of indole and amino acid-dependent CFPS. In this method, indole molecules in the assay sample are used to generate tryptophan, which is incorporated into signal-generating proteins in the subsequent cell-free synthesis reaction. The activity of cell-free synthesized proteins was successfully used to estimate the indole concentration in the assay sample. In principle, the developed method could be extended to analyses of other important bioactive compounds.